“Factores de riesgo obstétrico en primigestas adolescentes y su relación a complicaciones maternas, Hospital Básico Playas – Cantón Playas, octubre 2018 - abril 2019”. - Avilés Balbera, Yazmin Roció (2019)
Establish the relationship between obstetric risk factors in early adolescents and maternal complications, Playas Basic Hospital - Cantón Playas, October 2018 - April 2019. The research is basic, quantitative, deductive, descriptive, not experimental since it did not intervene on the study variables, they were only observed and related. The study population includes the pregnant primigrams adolescents being a total of 110 adolescent Primigestas that present obstetric risk factors. For the study on obstetric risk factors in early adolescents, adolescent patients whose parity represents more than one will be excluded as a total of 110 patients. To collect the data, an Excell spreadsheet was used to create a database that described the study variables used to empty the data contained in the RDACAA system (automated daily record of consultations and ambulatory care) according to the The objectives of the investigation. Our study shows that 69.10% of cases were with modifiable obstetric risk factors and 30.90% of cases with non-modifiable risk factors. With the following complications: Threat of abortion with 35 cases represented 31.81%, Preterm delivery with 20 cases representing 18.18%, Abortion with 12 cases representing 10.90%, Maternal death with 3 cases and a representation of 2.72%, Hemorrhage with 3 cases representing 2.72%, Anemia with 3 cases representing 2.72% and Malnutrition with 34 cases representing 30.90%.